2021
DOI: 10.1155/2021/6624874
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Kartogenin-Pretreated Infrapatellar Fat Pad Mesenchymal Stem Cells Enhance Chondrocyte Anabolism and Articular Cartilage Regeneration

Abstract: Objective. To evaluate the effect of Kartogenin-pretreated exosomes derived from infrapatellar fat pad mesenchymal stem cells on chondrocyte in vitro and articular cartilage regeneration in vivo. Methods. Infrapatellar fat pad mesenchymal stem cells (IPFP-MSCs) were isolated from rabbits to harvest exosomes. After identification of mesenchymal stem cells and exosomes, rabbit chondrocytes were divided into three groups for further treatment: the EXO group (chondrocytes treated with exosomes isolated from infrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…At 12 weeks after surgery, the rabbits were sacrificed under deep anesthesia, and femoral heads were isolated for imaging and macroscopic evaluation according to the guidelines of the International Cartilage Repair Society (ICRS) scoring system [ 20 ]. Subsequently, each femoral head was fixed in 4% PFA for 48 h and decalcified for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…At 12 weeks after surgery, the rabbits were sacrificed under deep anesthesia, and femoral heads were isolated for imaging and macroscopic evaluation according to the guidelines of the International Cartilage Repair Society (ICRS) scoring system [ 20 ]. Subsequently, each femoral head was fixed in 4% PFA for 48 h and decalcified for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Qiu et al found that miR-143 and miR-124 were upregulated in the mouse OA model after treatment of EVs derived from curcumin-treated MSC, and the normal expression of NF-kB and Rho-associated coiled-coil containing protein kinase 1 (ROCK1) was significantly restored, resulting in weakened progression of OA [ 55 ]. Studies have shown that EVs isolated from rabbit subpatellar fat pad mesenchymal stem cells pretreated with Kartogenin (KGN) have the effective ability to induce chondrogenic differentiation of stem cells, effectively promote the proliferation and expression of chondrogenic proteins and genes of chondrocytes, and are more effective to promote the repair of articular cartilage defects [ 56 ]. Similarly, EVs derived from KGN pretreated SD rat BMSC are more effective than EVs derived from BMSC in cartilage repair [ 57 ].…”
Section: Cell Pretreatment Strategymentioning
confidence: 99%
“…reported that EVs derived from kartogenin-preconditioned BMSCs enhanced chondral matrix synthesis and reduced degradation; thus this approach appears more effective for cartilage repair than the use of EVs from BMSCs without pretreatment with kartogenin [ 103 ]. A study using infrapatellar fat pad MSCs showed a similar result: EVs pretreated with kartogenin more effectively promoted articular cartilage defect repair [ 56 ]. Thus by altering the cellular environment through the addition of chemical compounds to the cell culture medium, the efficiency of the resultant EVs is improved.…”
Section: Delivery Strategies Of Evs In Cartilage Repairmentioning
confidence: 88%